2014
DOI: 10.5201/ipol.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Retinex

Abstract: While the retinex theory aimed at explaining human color perception, its derivations have led to efficient algorithms enhancing local image contrast, thus permitting among other features, to "see in the shadows". Among these derived algorithms, Multiscale Retinex is probably the most successful center-surround image filter. In this paper, we offer an analysis and implementation of Multiscale Retinex. We point out and resolve some ambiguities of the method. In particular, we show that the important color correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(124 citation statements)
references
References 17 publications
0
104
0
4
Order By: Relevance
“…Third, we apply the gain/offset function (Eqation (3)) before the color processing function, in contrast to [7] where the order of the two operations is reversed (i.e., we use I Ret i (x) in Equation (6), instead of R i (x, c)). We found that this prevents from color conversion issues for images that contain saturated colors, compared to the original color processing scheme [7,20]. In Figure 4, we show an example of an image that contains pixels with saturated colors, for example, pixels of the blue balls with I R = 0 (Figure 4a).…”
Section: Color Processing Function Combining Retinex and Gray Worldmentioning
confidence: 99%
“…Third, we apply the gain/offset function (Eqation (3)) before the color processing function, in contrast to [7] where the order of the two operations is reversed (i.e., we use I Ret i (x) in Equation (6), instead of R i (x, c)). We found that this prevents from color conversion issues for images that contain saturated colors, compared to the original color processing scheme [7,20]. In Figure 4, we show an example of an image that contains pixels with saturated colors, for example, pixels of the blue balls with I R = 0 (Figure 4a).…”
Section: Color Processing Function Combining Retinex and Gray Worldmentioning
confidence: 99%
“…Um exemplo de como nosso sistema de visão é relativo pode ser avaliado na ilusão de ótica da Figura 10, onde o quadrado A e D possuem a mesma intensidade. Além do estudo fisiológico, a teoria foi proposta para obtenção de uma análoga constância luminosa em sistemas de visão de máquina, caracterizando o Retinex como uma estratégia para processamento de imagem, gerando realce de luminosidade e cor para imagens digitais (AGARWAL et al, 2006;KOSCHAN;ABIDI, 2008;PETRO;SBERT;MOREL, 2014).…”
Section: Retinexunclassified
“…Fazendo uso deste operador gaussiano como função de cálculo de região normalizada, um primeiro método, conhecido como Single-Scale Retinex (SSR) pode ser explorado (RAHMAN; WOODELL, 2004;PETRO;SBERT;MOREL, 2014). Sua forma matemática, a ser estendida para todos os canais da imagem, é dada por:…”
Section: Retinexunclassified
See 1 more Smart Citation
“…They usually enhance the contrast in each pixel depending on the information of its local neighborhood, with the aim of isolating the effects on dark and bright regions. Local image contrast methods are usually based on human perception, like, e.g., the multiscale retinex method [9,13].…”
Section: Introductionmentioning
confidence: 99%